Progress made in the implementation of the outcomes of the major United Nations conferences and summits, and UNCTAD contributions (UN New YorkUS, 2012)
Provides a brief overview of the progress made in the relevant thematic areas and UNCTAD's contributions to the outcomes.
Note by the UNCTAD Secretariat.